Correction of endothelial dysfunction and microcirculation disturbances in patients with essential arterial hypertension and Type 2 diabetes mellitus - N. V. Yakutina (Российский кардиологический журнал)
In total, 145patients with Stage 3 essential arterial hypertension (AH) were examined, including 55 individuals without diabetes mellitus (DM), 90 subjects with AH and severe Type 2 DM (in 34, total or partial plantar amputation was performed, due to diabetic foot syndrome). In patients with AH and Type 2 DM, lower extremity microcirculatory blood flow was significantly reduced; pathological microcirculation types and severe endothelial dysfunction (laser Doppler flowmetry and plasma markers) were maximally manifested in individuals after amputation. Simvastatin therapy, as a part of complex treatment, improved lower extremity microcirculation and endothelial function inpatients with AH, Type 2 DM, and normostatic or congestive-spastic microcirculation types.